If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26x + 21 = 32x + -9 Reorder the terms: 21 + 26x = 32x + -9 Reorder the terms: 21 + 26x = -9 + 32x Solving 21 + 26x = -9 + 32x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-32x' to each side of the equation. 21 + 26x + -32x = -9 + 32x + -32x Combine like terms: 26x + -32x = -6x 21 + -6x = -9 + 32x + -32x Combine like terms: 32x + -32x = 0 21 + -6x = -9 + 0 21 + -6x = -9 Add '-21' to each side of the equation. 21 + -21 + -6x = -9 + -21 Combine like terms: 21 + -21 = 0 0 + -6x = -9 + -21 -6x = -9 + -21 Combine like terms: -9 + -21 = -30 -6x = -30 Divide each side by '-6'. x = 5 Simplifying x = 5
| 3x^2+10x=32 | | 1/9y=-7 | | -4(y-9)=-10(2-y) | | x=4x+2 | | z-1/2=-1/4 | | .3x-4.2=2.4 | | .3-4.2=2.4 | | 60-2x=30 | | 12/18 | | 6-66.6666666667x=-8 | | 19+0+(-9)= | | 6/18+3/19 | | 8/11-4/15 | | 4/9+m=20 | | y=-5x^2+30t+2 | | 2*3*4*5= | | 3x-23=1-4x | | 4/16+2/13 | | 4y+8x=48 | | 3x-2(x+4)=-1 | | 14/15-4/12 | | 5x-11=-11 | | 3/4x+2/9-3/7 | | -4x-21=3x+7 | | 7/20+3/9 | | 2450:345= | | 2-1/2(4x+6)=5x-1 | | 6(-t-1)=9(t-4) | | 9x+5=3x+6 | | 8x+4y=48 | | 11x-3(5x-4)=2+6(x+5) | | 2ln(x)-ln(5)=ln(x+10) |